Diferences in decisions afected by cognitive biases : examining human values, need for cognition, and numeracy - Kakinohana, Regis Kichei (2023)
A better understanding of factors that can afect preferences and choices may contribute to more accurate decision making. Several studies have investigated the efects of cognitive biases on decision-making and their relation ship with cognitive abilities and thinking dispositions. While studies on behaviour, attitude, personality, and health worries have examined their relationship with human values, research on cognitive bias has not investigated its relationship to individual diferences in human values. The purpose of this study was to explore individual diferences in biased choices, examining the relationships of the human values self-direction, conformity, power, and universal ism with the anchoring efect, the framing efect, the certainty efect, and the outcome bias, as well as the mediation of need for cognition and the moderation of numeracy in these relationships. We measured individual diferences and within-participant efects with an online questionnaire completed by 409 Brazilian participants, with an age range from 18 to 80 years, 56.7% female, and 43.3% male. The cognitive biases studied consistently infuenced choices and preferences. However, the biases showed distinct relationships with the individual diferences investigated, indicating the involvement of diverse psychological mechanisms. For example, people who value more self-direction were less afected only by anchoring. Hence, people more susceptible to one bias were not similarly susceptible to another. This can help in research on how to weaken or strengthen cognitive biases and heuristics.